Nature-Based Sensory Play as an Intervention for Fine Motor Skills Development in Early Childhood - Halimah, Nur; Chamidah, Atien Nur (Papanda Publisher, 2025)
Fine motor skills development during early childhood is crucial for academic readiness and daily functioning. This study investigated the effects of nature-based sensory play interventions on fine motor skills development in preschool children with identified motor difficulties. A pre-experimental one-group pretest-posttest design was employed with three participants aged 4-5 years from TK Negeri 2 Muara Ancalong who demonstrated fine motor skill challenges. The intervention consisted of three structured sensory play sessions using natural materials including sand, clay, stones, and organic matter. Fine motor skills were assessed using seven indicators including object manipulation, tool usage, pincer grasp, grip strength, and sustained attention. Data analysis employed descriptive statistics and N-Gain calculations. All participants demonstrated substantial improvements from pretest to posttest. Mean scores increased from 16.67 to 25.67 (maximum 28), representing a gain of 9.0 points. N-Gain analysis yielded 0.83, indicating high-level improvement effectiveness. Individual participants showed consistent progress across all measured indicators, with enhanced object transfer stability, improved tool control, more precise pincer movements, and increased task persistence. Progressive improvement was observed across treatment sessions, with reduced need for external motivation and enhanced concentration capabilities. Nature-based sensory play interventions effectively enhanced fine motor skills development in children with identified difficulties. The multidimensional improvements support theoretical frameworks linking motor skill development to cognitive abilities and academic readiness. Results align with research demonstrating connections between fine motor skills and executive functions, mathematical reasoning, and written expression abilities.